Quality seed of vegetables brings dividends - Singh, P. M.; Manimurugan, Manimurugan; Chaubey, T.; Kumar, Rajesh; Singh, Vikas; Gupta, Nakul (Indian Horticulture, 2019)
With increasing consciousness of the masses towards the health and nutritional security, the consumption of vegetables has increased over the years. Although vegetable production has also increased with time, shrinking land resources has made the use of quality seeds more important to keep abreast with the accelerating demand of vegetables by Indian populace.